Single-phase controlled AC-DC converter using SCR - Irsyad, Muhammad; Krismadinata (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The 1-phase controlled full-wave rectifier is one of the main components in power electronics technology that functions to convert alternating voltage (AC) into direct voltage (DC). This circuit is used in various applications, such as battery charging systems and DC motors in industry. Controlled rectifiers use a Silicon Controlled Rectifier (SCR). The use of SCRs in controlled rectifiers provides the advantage of more precise current control. The controlled rectifier uses a Silicon Controlled Rectifier (SCR), which is controlled with a microcontroller through an SCR driver. The SCR driver serves for isolation so that the converter circuit does not damage the microcontroller due to current surges. This circuit also requires a zero crossing detector to determine the intersection of point 0 on the AC wave. This research aims to design and build a 1-phase full wave rectifier system using SCR as the main controlling component. With a deep understanding of SCR characteristics, it is hoped that this research can contribute to the development of modern power supply technology that is more efficient and can be controlled with precision.